Ruling the streets: the policing of protest and political violence in Madrid during the Second Republic, 1931-1936 - Sergio Vaquero Martínez (Culture & History Digital Journal)
The state has occupied a privileged space in most of the explanations regarding the origins of the political violence that disrupted the course of the Spanish Second Republic. Nevertheless, the generalised notion that the majority of deaths were the outcome of the repression of popular mobilisation contrasts with the practical inexistence of studies devoted to the specific interactions between coercive forces and collective challengers. With the purpose of partially filling this gap, the following article analyses the policing of protest in the province of Madrid from 14 April 1931 to 17 July 1936. The research relies on a database of approximately 450 recorded events that has been constructed from a corpus of archival documentation from the Ministry of the Interior, contemporary newspapers and specialised monographs. This article argues that the mistakes, dysfunctions and collateral effects of the policing of social protests derived from the restoration of a lethal, military repertoire of coercion and, more indirectly, the invention of a civil, non-lethal style. The incoherent alternation of both repertoires followed politically motivated criteria and fostered an escalation of violence that increased the number of victims and obstructed the democratisation of the security apparatus.